MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Zulfan Hanif Rahman; Reni Setyaningsih (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mastering problem-solving skills is important for students in the 21st century. The RME approach can be an alternative to improve students' problem-solving skills. This study aims to determine the effect of the RME approach on students' problem-solving skills. This study used a one-group pre-test post-test design. It involved 30 students of class III at State Elementary School Jombatan 3. Data were collected by pre-test and post-test of problem-solving skills. The results of the descriptive analysis show an increase in the average problem-solving skills score of 29.8 after the use of the RME approach in learning. Data were analyzed using a t-test. The t-test obtains a significance level of 0.000 <0.05 meaning that is rejected and is accepted. Thus, there is a difference in the mean score of problem-solving skills before and after the use of the RME approach in learning. This proves that students' problem-solving skills increase after the use of the RME approach in learning. The application of the RME approach can improve one’s higher order thingking skills.